Electrical Driving and Control System of HXN6 High-power Hybrid Diesel Locomotive - SHANG Jing; HE Liang; LIU Shunguo; LI Xiaowen; WANG Pinghua (机车电传动)
HXN6 locomotive is a high-power AC drive hybrid diesel locomotive developed for railways in China, and it is also the largest power hybrid diesel locomotive at present. Large capacity lithium iron phosphate battery was used as power battery for locomotive, and power supply was combined with diesel engine. The new main auxiliary drive integrated circuit and control technology were adopted. The structure and technical characteristics of HXN6 locomotive traction main drive system, microcomputer network control system and auxiliary drive system were introduced in detail. Locomotive in the test and application of the appraisal process showed excellent performance in energy saving and emission reduction.